Filter Cerobong Asap Cyclone Dust Collector untuk Mengurangi Emisi Insinerator - Jayadi, Hurip (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Improving air quality is a major challenge in air sanitation. Incinerator is a waste burning device that produces emissions such as particulates, sulfur dioxide gas (SO₂), nitrogen oxide (NOₓ), carbon monoxide (CO) which have the potential to pollute the environment and endanger health. This study aimed to test the effectiveness of various variations in the depth of the cyclone dust collector chimney filter pipe to reduce incinerator emissions. This study used a simple experimental design, which was conducted at a public health center. The test was carried out by burning medical solid waste in an incinerator, with variations in the depth of the chimney filter pipe being 40 cm, 60 cm and 80 cm. The incinerator emissions measured were SO2, NOx and CO gases, which were taken using a migget impinger. Examination of particulates and gases was carried out using the graphometric and spectrophotometer methods, respectively. Differences in emissions were analyzed descriptively. The results of the analysis showed that in 3 variations in pipe depth; the total particulates were 250, 180 and 125 (quality standard = 120); SO2 is 343, 298 and 245 (standard = 210); NOx is 522, 490 and 450 (standard = 470); CO is 753, 693 and 630 (standard = 625). It can be seen that in all variations of pipe depth, all emission indicators that were previously above the standard have decreased below the standard. The increasing depth of the pipe further reduces emissions. It is concluded that the cyclone dust collector is successful in reducing incinerator emissions, with the best results in the deepest pipe.Keywords: chimney filter; cyclone dust collector; incinerator emissions ABSTRAK Peningkatan kualitas udara menjadi tantangan utama dalam penyehatan udara. Insinerator merupakan alat pembakar sampah menghasilkan emisi seperti partikulat, gas sulfur dioksida (SO₂), nitrogen oksida (NOₓ), karbon monoksida (CO) yang berpotensi mencemari lingkungan dan membahayakan kesehatan. Penelitian ini untuk menguji efektivitas berbagai variasi kedalaman pipa filter cerobong asap cyclone dust collector untuk mengurangi emisi  insinerator. Studi ini menggunakan rancangan eksperimen sederhana, yang dilakukan di pusat kesehatan masyarakat. Pengujian dilakukan dengan membakar limbah padat medis pada insinerator, dengan variasi kedalaman pipa filter cerobong asap adalah 40 cm, 60 cm dan 80 cm. Emisi insinerator yang diukur adalah gas SO2, NOx dan CO, yang diambil menggunakan migget impinger. Pemeriksaan partikulat dan gas masing-masing dilakukan dengan metode grafimetri dan spektrofotometer. Perbedaan emisi dianalisis secara deskriptif. Hasil analisis menunjukkan bahwa pada 3 variasi kedalaman pipa; total partikulat adalah 250, 180 dan 125 (baku mutu = 120); SO2 adalah 343, 298 dan 245 (baku mutu = 210); NOx adalah 522, 490 dan 450 (baku mutu = 470); CO adalah 753, 693 dan 630 (baku mutu = 625). Terlihat bahwa pada semua variasi kedalaman pipa, semua indikator emisi yang sebelumnya di atas baku mutu telah menurun di bawah baku mutu. Bertambahkanya kedalaman pipa, semakin menurunkan emisi. Disimpulkan bahwa cyclone dust collector berhasil menurunkan emisi insinerator, dengan hasil terbaik pada pipa terdalam.Kata kunci: filter cerobong asap; cyclone dust collector; emisi insinerator